Substance Use and Rural Populations - Erin Kersey; Latoya J. O'Neal; Ashlyn Michael; Beatrice Pierre; Tyler Nesbit; Larry Forthun (EDIS, 2023)
This article aims to describe the impact of substance use on rural communities, to share knowledge of the unique challenges rural populations face, to highlight the need for prevention efforts geared towards adolescents, and to inform Extension professionals about current UF/IFAS initiatives. Written by Erin Kersey, LaToya J. O’Neal, Ashlyn Michael, Beatrice Pierre, Tyler Nesbit, and Larry Forthun, and published by the UF/IFAS Department of Family, Youth and Community Sciences, February 2023.